Efficacy of Vacuum Assisted Dressing Technique in the Treatment of Diabetic Foot Ulcers - Hassan, Shah; Hussain, Muhammad; Sidra; Khan, Abdul Basit; Adil ur Rehman; Khan, Awais (Indus Journal of Bioscience Research, 2025)
Background: Diabetic foot ulcers (DFUs) provide significant care issues due to their delayed healing durations and high complication rates. The purpose of this study is to assess the effectiveness of vacuum-assisted dressing in enhancing DFU healing and to identify factors that influence outcomes. Objective: To determine the efficacy of vacuum assisted dressing technique in the treatment of diabetic foot ulcers. Study Design and Setting: A quasi-experimental study was conducted at the Department of Surgery, Mardan Medical Complex Mardan from July 2024 to December 2024. Materials and Methods: The study included 85 patients with DFUs, with an average age of 58.3 years (SD ± 12.5) and diabetes duration of 10.8 years (SD ± 6.3). Demographic, clinical, and treatment data were analyzed. The key outcomes were healing time, ulcer size decrease, pain reduction, and complication rates. Regression analysis was used to find determinants of healing. Results: This study involved 85 patients with diabetic foot ulcers (mean age 58.3 years, average diabetes duration 10.8 years). Vacuum-assisted dressing led to significant healing, with a mean healing time of 8.5 weeks and >50% ulcer size reduction in 64.7% of patients. Pain scores dropped by 2.3 points, and satisfaction was high. Significant predictors of healing time included age, smoking, Wagner grade, ulcer size, and infection, with vacuum-assisted dressing significantly shortening healing time (β = -2.5, p < 0.001). Conclusions: Vacuum-assisted dressing is a successful and patient-friendly approach for controlling DFUs that reduces healing time, ulcer size, and complications. Early intervention and addressing modifiable risk factors are crucial for achieving optimal outcomes.